A dark and lonely place [compact disc, unabridged] - Buchanan, Edna (Dreamscape Media, 2011)
In Miami, Police Detective Sgt. John Ashley hunts a woman linked to a murdered millionaire and finds she is the girl who's haunted his dreams since childhood. A century ago on America's southern frontier, John Ashley's ancestor was wrongly accused of murder and went on the run with his sweetheart. The lovers became the most colorful, compelling, and heartbreaking figures in Florida's violent outlaw history. Can the present-day couple break the tragic cycle imprinted on their DNA?